Oasis desert farming selects environment‐specific date palm root endophytic communities and cultivable bacteria that promote resistance to drought. Issue 4 (August 2015) - Cherif, Hanene; Marasco, Ramona; Rolli, Eleonora; Ferjani, Raoudha; Fusi, Marco; Soussi, Asma; Mapelli, Francesca; Blilou, Ikram; Borin, Sara; Boudabous, Abdellatif; Cherif, Ameur; Daffonchio, Daniele; et al.
Summary Oases are desert‐farming agro‐ecosystems, where date palm (Phoenix dactylifera L.) plays a keystone role in offsetting the effects of drought and maintaining a suitable microclimate for agriculture. At present, abundance, diversity and plant growth promotion (PGP) of date palm root‐associated bacteria remain unknown. Considering the environmental pressure determined by the water scarcity in the desert environments, we hypothesized that bacteria associated with date palm roots improve plant resistance to drought. Here, the ecology of date palm root endophytes from oases in the Tunisian Sahara was studied with emphasis on their capacity to promote growth under drought. Endophytic communities segregated along a north–south gradient in correlation with geo‐climatic parameters. Screening of 120 endophytes indicated that date palm roots select for bacteria with multiple PGP traits. Bacteria rapidly cross‐colonized the root tissues of different species of plants, including the original Tunisian date palm cultivar, Saudi Arabian cultivars and Arabidopsis. Selected endophytes significantly increased the biomass of date palms exposed to repeated drought stress periods during a 9‐month greenhouse experiment. Overall, results indicate that date palm roots shape endophytic communities that are capable to promote plant growth under drought conditions, thereby contributing an essential ecological service to the entire oasis ecosystem.